Integrated Grain and Forage Rotations - J. D. Holman; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2016)
Producers are interested in growing forages in rotation with grain crops. Many producers are interested in diversifying their operations to include livestock or grow feed for the livestock industry. By integrating forages into the cropping system, producers can take advantage of more markets and reduce market risk. Forages require less water to make a crop than grain crops, so the potential may exist to reduce fallow by including forages in the crop rotation. Reducing fallow through intensified grain/forage rotations may increase the profitability and sustainability compared to existing crop rotations. This study was started in 2013, with crops grown in-phase beginning in 2014. Grain crops were more sensitive to moisture stress than forage crops. Growing a double-crop forage sorghum after wheat reduced grain sorghum yield the second year, but never reduced second-year forage sorghum yield in the years of this study. As long as double-crop forage sorghum is profitable, it appears the cropping system can be intensified by growing second year forage sorghum. Caution should be used when planting double-crop forage sorghum by evaluating soil moisture condition and precipitation outlook, since other research has found cropping intensity should be reduced in dry years. The “flex-fallow” concept could be used to make a decision on whether or not to plant double-crop forage sorghum to increase the chance of success. Of important note, this research showed forages are more tolerant to moisture stress than grain crops and the potential exists to increase cropping intensity by integrating forages into the rotation.
Keywords: grain and forage rotations; irrigation management; forage crops; profitability and sustainability in crop rotations